Map-based Mobile Services Theories, Methods and Implementations - Meng, Liqiu; Zipf, Alexander; Reichenbacher, Tumasch (Springer Berlin Heidelberg : Imprint: Springer, 2005)
The development of wireless telecommunication and ubiquitous computing te- nologies has led to a growing mobile population and dramatically changed p- terns of working and everyday life. A smooth and safe mobility is only possible when the mobile person is well-informed of the happenings in his ambient en- ronments. Location-sensitive maps have proved a strong enhancement to what a mobile user can directly perceive from his ambient environments. Since ancient times the map has been the favorite communication language of spatial infor- tion. It is even more the case for mobile applications where brand-new maps can be wirelessly retrieved or generated in real-time. The upsurge of map-based s- vices on mobile devices has raised a number of new questions challenging the conventional computer-assisted cartography. Map-based mobile services provides a contemporary overview of research and development issues related to the design and the use of mobility-supporting maps. The book has been written for professional cartographers who are striving for - tending their theoretical, methodological and practical knowledge to mobile m- making, for surveyors and geo-service providers involved in the development of intelligent location-based services, for software developers and cognitive scientists engaged in human-computer interaction, and for students and academics in cart- raphy and geoinformation sciences. The book was initiated by the multidisciplinary workshop "Design of m- based mobile services" within the frame of the conference "Human and Computer 2003 - Interaction on the movement" held in Stuttgart, Germany, September 2003.